Infantile loss of teeth: odontohypophosphatasia or childhood hypophosphatasia - BEREKET, ABDULLAH; HALİLOĞLU, BELMA; DEMİRCİOĞLU, SERAP; GÜRAN, TÜLAY (SPRINGER, 2013)
Hypophosphatasia is a hereditary disorder characterized by a deficiency of serum and bone alkaline phosphatase (ALP) activity and defective skeletal mineralization. It is caused by a loss of function mutations in the tissue nonspecific ALP gene (TNSALP) encoding the tissue nonspecific alkaline phosphatase. A 4-year-and-8-month-old girl presented with premature exfoliation of the anterior incisors and canines. Very low ALP level (27 IU/ml) suggested the diagnosis of hypophosphatasia, which was supported by an elevated urine phosphoethanolamine/Cr of 84 mu mol/mmol (reference range, < 25 mu mol/mmol) and serum pyridoxal-5'-phosphate of 393 mu g/L (reference range, 3.6-18 mu g/L). The phenotype of the patient was subsequently classified as mild childhood hypophosphatasia. TNSALP gene sequencing revealed the homozygous c.382 G > A (p.V128M) mutation. This mutation was previously observed in a series of patients with severe hypophosphatasia, pointing out the possible role of other genetic or environmental factors in the modulation of the hypophosphatasia phenotype.
Keywords: Hypophosphatasia; Tooth; Odontohypophosphatasia; Infantile teeth loss; ALKALINE-PHOSPHATASE; PHENOTYPE; GENOTYPE